The 9p21 Myocardial Infarction Risk Allele Increases Risk of Peripheral Artery Disease in Older People - Christie Cluett; Mary Mcdermott; Jack M. Guralnik; Luigi Ferrucci; Stefania Bandinelli; Iva Miljkovic; Joseph M. Zmuda; Rongling Li; Greg Tranah; Tamara Harris; Neil Rice; William Henley; et al. (2009)
A common variant at chromosome 9p21 (tagged by the rs1333049 or rs10757278 single-nucleotide polymorphism) is strongly associated with myocardial infarction and major arterial aneurysms. An association with peripheral arterial disease (PAD) was also reported in a sample younger than 75 years, but this disappeared on removal of respondents with a myocardial infarction history, resulting in an odds ratio of 1.09 for PAD (P=0.075). We aimed at estimating the association of this variant with an Ankle-Brachial Index (ABI) and PAD in 3 older populations.We used data from the InCHIANTI, Baltimore Longitudinal Study of Aging, and Health, Aging, and Body Composition studies. In 2630 white individuals (mean age, 76.4 years), the C allele at rs1333049 was associated with lower mean ABI measures and with an increased prevalence of PAD. These associations remained after removal of baseline and incident myocardial infarction cases over a 6-year follow-up for both ABI (-0.017 ABI units; 95% CI, -0.03 to -0.01; P = 1.3 x 10(-4)) and PAD (per allele odds ratio, 1.29; 95% CI, 1.06 to 1.56; P = 0.012). These associations also remained after adjustment for known atherosclerosis risk factors, including diabetes mellitus, smoking, hypercholesterolemia, and hypertension.The C allele at rs1333049 is associated with an increased prevalence of PAD and lower mean ABI. This association was independent of the presence of diagnosed myocardial infarction and atherosclerotic risk factors in 3 older white populations.